2010
DOI: 10.4028/www.scientific.net/ast.64.65
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Development of Resource-Saving High Performance Slurry - Polishing/CMP for Glass Substrates in a Radical Polishing Environment, Using Manganese Oxide Slurry as an Alternative for Ceria Slurry

Abstract: While investigating polishing mechanism of glass substrates with ceria abrasives (CeO2), we found its oxidizing properties worked effectively for the polishing. This finding has inspired us to speculate about the possibility of the manganese oxide abrasives as an alternative for ceria as they also have oxidizing properties. Therefore, focusing on the valence of the manganese, we have experimentally manufactured MnO, MnO2, Mn2O3 and Mn3O4 abrasives, and conducted a comparison study of the characteristics obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…It needs to be noted that in 500kPa air atmosphere, as N 2 existing in the air bears most partial pressure, thus the solubility of O 2 in the slurry is affected and the material removal rate in such atmosphere is lower than that in pure O 2 high-pressure atmosphere. 17,[23][24][25] Through analysis of the experimental results mentioned above, it can be concluded that the Si substrate material removal rate of CMP can be increased by changing the processing atmosphere (gas pressure and gas componenents) and the main influential factor is the increase of O 2 partial pressure, which can cause the concentration of DO in the slurry to increase. and high-pressure O 2 atmosphere respectively for 24-hour dissolution test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It needs to be noted that in 500kPa air atmosphere, as N 2 existing in the air bears most partial pressure, thus the solubility of O 2 in the slurry is affected and the material removal rate in such atmosphere is lower than that in pure O 2 high-pressure atmosphere. 17,[23][24][25] Through analysis of the experimental results mentioned above, it can be concluded that the Si substrate material removal rate of CMP can be increased by changing the processing atmosphere (gas pressure and gas componenents) and the main influential factor is the increase of O 2 partial pressure, which can cause the concentration of DO in the slurry to increase. and high-pressure O 2 atmosphere respectively for 24-hour dissolution test.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to design and develop CMP techniques that are suitable for these new materials has become a focus of the researchers, and outstanding achievements have been made through extensive researches. For example, Professor Doi et al used high-speed equipment in conjunction with high-pressure device to polish power semiconductor materials at high speed in order to increase the processing efficiency mechanically, the material removal rate was improved significantly and high-quality z E-mail: yintaoyy120@gmail.com surface was obtained; 13,14 Professor Babu and Yin et al employed the chemical efficiency-increasing method, in which strong oxidant was added to corrode the copper substrate and the silicon carbide substrate, and the processing quality and efficiency were improved significantly; [15][16][17][18][19][20] Professor Lee used multicrystalline diamond slurry to process the sapphire substrate, and the material removal rate was improved significantly while ensuring the processing quality. 21,22 However, for those methods mentioned above, almost all CMP processes were carried out in open environments and the impact of processing environments on the entire CMP process was neglected.…”
mentioning
confidence: 99%
“…As manganese oxide has been revealed to have some interesting characteristics, several corresponding studies have been performed. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Some of these studies reported that manganese oxide slurry polishes several materials such as tungsten, copper, SiO 2 , and low dielectric constant materials.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 DOI and SESHIMO developed a CMP/plasmachemical vaporization machining (CMP/P-CVM) method that significantly increased the removal efficiency and surface quality of SiC substrates. 12,13 Wang et al used femtosecond-laser-irradiationassisted CMP to improve material removal by destabilizing surface crystals. 14 Yuan et al used UV-TiO 2 -photocatalysis-assisted CMP to increase the material removal rate and surface quality of 4H-SiC wafers.…”
mentioning
confidence: 99%